(untitled) (Journal of Dhaka National Medical College & Hospital, 2019)
Background: The gradual increase of Dengue fever among children of our country is a growing challenge of child health. Dengue fever causes considerable morbidity and mortality and a leading cause of hospitalisation during its outbreak. Therefore we aimed at a study of features and outcome of Dengue fever among children admitted in our hospital. Objectives: The objective of the study was to study the features and outcome of Dengue viral illness for better understanding and efficient management of the disease for improvement of child health service. Materials and methods: Between 4th September to 26th December 2018, we conducted this study among children admitted in Pediatric ward of Dhaka National Medical College Hospital. Diagnosis was established by careful history taking, Physical examination and suitable laboratory investigations. Clinical features, laboratory findings and treatment outcome were studied and subsequent statistical significance was analyzed. Results: Out of 108 study patients, 3 (2.78%) were <1 year of age, 44 (40.74%) were 1-5 year of age and 61 (56.68%) were above 5 years of age. Duration of fever was 1-2 days in 12 (11.11%), 3-5 days in 53 (49.07%) and >5 days in 39.81%, 33 children had fever <100° F (30.56%), 49 children’s had fever 100-102° F (45.37%) and 26 (24.07%) had fever >102° F. There was cutanuous bleeding in 13 (9.26%), mucosal bleeding 6 (5.56%) and internal haemorrhage in 7 (6.48% ), Platelet count were>1,00,000 in 62 (57.04% ), 50,000-1,00,000 in 27 patients (25%) and <50,000 in 19 (17.59%). Classical Dengue fever, Dengue haemorrhagic fever and Dengue shock syndrome were 77%, 21% and 2% respectively. Conclusion: This study observes the clinical features, laboratory abnormalities and treatment outcome of those children who were admitted in pediatric ward of our hospital. Larger multicentral and long term study and evaluation of Dengue viral illness among our population will effect great impact in management of this disease. J. Dhaka National Med. Coll. Hos. 2019; 25 (01): 40-42